Dinâmicas empresariais: um olhar antropológico sobre o processo seletivo para trainee Jovens Talentos Natura 2014 - Viana, Karine Dutra Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The hypothesis that guides this work is: in the scenario posed by the first decade of the XXI century, the private companies act to conciliate their organizational principles, mission (how they want to arrive), vision (where they want to arrive) and values to the principles of its individual members, setting a certain style of corporate culture. That culture would pass by all hierarchical levels of enterprises, promoting the creation of subjective bonds between themselves and their employees in order to create or maintain, through shared values, social conventions that would ensure the certain style of symbolic domination inside and outside the physical and relational enterprises' spaces. I have as general objective, analyze, through a socio-anthropological approach, the dimension of the culture of private companies, how this guides the market practice and, in this sense, I seek to problematize the relationship between the actions of the analyzed companies (Nestle and, more specifically, Natura) and the representations and motivations of their employees. Furthermore, this study aims, specifically, to understand how the vision, the raison of being and the beliefs of Natura configure themselves as important strategic directives for the consolidation of an emotional bond between employees and those who aspire to be part of this organization. For this, I analyzed the Report Natura 2012, the conversations with some company employees and my participation in the selection process for trainee Young Talents Natura 2014

A hipótese que norteia este trabalho é a de que no cenário posto pela primeira década do século XXI, as empresas privadas agem de forma a conciliar seus princípios organizacionais, missão (como se quer chegar), visão (onde se quer chegar?) e valores aos princípios individuais de seus membros, configurando assim um certo estilo de cultura empresarial. Tal cultura perpassaria todos os níveis hierárquicos das empresas, favorecendo a criação de vínculos subjetivos entre estas e seus funcionários, de modo a criar ou manter, a partir dos valores compartilhados, convenções sociais capazes de assegurar um certo estilo de dominação simbólica dentro e fora do espaço físico e relacional das empresas. Tenho como objetivo geral, analisar, por meio de uma abordagem sócioantropológica, a dimensão da cultura das empresas privadas, o modo como esta direciona as práticas no mercado e, neste sentido, procuro problematizar a relação entre as ações das empresas analisadas (Nestlé e, mais especificamente, a Natura) e as representações e motivações de seus funcionários. Outrossim, este trabalho tem como objetivo específico compreender de que forma a visão, a razão de ser, e as crenças da Natura se configuram como diretrizes estratégicas importantes para a consolidação de um vínculo afetivo entre seus funcionários e aqueles que aspiram fazer parte desta organização. Para isso me pautei pela análise do Relatório Natura 2012, de conversas com funcionários da empresa e da minha participação no processo seletivo para trainee Jovens Talentos Natura 2014
Keywords: Natura Cosméticos S.A; Antropologia; Cultura organizacional; Anthropology